Even Worse — Risk Factors and Protective Factors for Transition from Chronic Localized Low Back Pain to Chronic Widespread Pain in General Practice. Issue 15 (1st August 2015) - Viniol, Annika; Jegan, Nikita; Brugger, Markus; Leonhardt, Corinna; Barth, Jürgen; Baum, Erika; Becker, Annette; Strauch, Konstantin
<x xml:space="preserve">Abstract</x> Study Design. Prospective cohort study with patients with chronic low back pain (CLBP) at primary care setting. Objective. The aim of our study was to identify predictors for transition from localized CLBP to chronic widespread pain in general practice. In contrast to the typically investigated risk factors, this study also focuses intensively on protective factors, which decrease the probability of chronic widespread pain. For this, we investigated the resources resilience and coping strategies, which are suspected as potential protective factors for incident chronic pain syndromes. Summary of Background Data. In primary care, about a quarter of patients with CLBP experience chronic widespread pain (CWP). Methods. Patients experiencing localized CLBP were included and evaluated after a 6- and 12-month follow-up period regarding the development of CWP. Potential risk factors (sociodemographic data, pain characteristics, depression, anxiety, somatization), protective factors (resilience, coping strategies), and sample characteristics were assessed at baseline. Predictor identification was done by multivariate logistic regression analysis. Results. The 1-year incidence for the onset of CWP among patients with CLBP was 23.8%. We identified the 3 risk factors, female sex, long duration of back pain, and a high rate of psychosomatic symptoms, for the onset of CWP among patients with CLBP. Coping resources and resilience had no impact on the transition from CLBP to CWP. Conclusion. The results suggest that CWP is no independent entity but rather a particularly negative occurrence on a continuum of chronic pain. Processes of somatization play a major role in the development of this extreme. Level of Evidence: 2